Option Momentum - HESTON, STEVEN L.; JONES, CHRISTOPHER S.; KHORRAM, MEHDI; LI, SHUAIQI; MO, HAITAO (Journal of Finance, 2023)
ABSTRACT This paper investigates the performance of option investments across different stocks by computing monthly returns on at‐the‐money straddles on individual equities. We find that options with high historical returns continue to significantly outperform options with low historical returns over horizons ranging from 6 to 36 months. This phenomenon is robust to including out‐of‐the‐money options or delta‐hedging the returns. Unlike stock momentum, option return continuation is not followed by long‐run reversal. Significant returns remain after factor risk adjustment and after controlling for implied volatility and other characteristics. Across stocks, trading costs are unrelated to the magnitude of momentum profits.